Antiviral activity and mechanism of gossypols: effects of the O2˙− production rate and the chirality. Issue 17 (7th February 2017) - Zhang, Bin; Liu, Yuxiu; Wang, Ziwen; Li, Yongqiang; Wang, Qingmin
Abstract : (−)-Gossypol displayed an obviously higher antiviral activity against the tobacco mosaic virus (TMV) than (+)-gossypol, whereas the anti-TMV activity of (−)-gossypol Schiff bases is not significantly higher than (+)-gossypol Schiff bases. Abstract : (−)-Gossypol displayed an obviously higher antiviral activity against the tobacco mosaic virus (TMV) than (+)-gossypol, whereas the anti-TMV activity of (−)-gossypol Schiff bases is not significantly higher than (+)-gossypol Schiff bases. A mechanism study indicated that these gossypol compounds could neither inhibit the multiplication of TMV nor induce the systemic acquired resistance of tobacco plants. However, gossypol compounds with high anti-TMV activities could induce the accumulation of reactive oxygen species (ROS) in tobacco leaves, and this result is in accordance with the characteristics of extreme resistance featuring a necessary early and rapid ROS (O2 ˙ − or H2 O2 ) accumulation in plants. Further study showed that, the anti-TMV activities of the test compounds decreased synchronously when the O2 ˙ − accumulation was reduced by superoxide dismutase (SOD). However, when the H2 O2 accumulation was suppressed by hydrogen peroxidase (CAT), the anti-TMV activities did not change. Therefore, compared with the H2 O2 accumulation in gossypol compounds-treated tobacco leaves, the O2 ˙ − accumulation is a key factor for the development of the anti-TMV activities of those compounds, and their anti-TMV mechanism belonged to their extreme resistance. Further study showed that the O2 ˙ − accumulation in the (−)-gossypol-treated tobacco leaves was mainly from the tobacco itself, whereas the same O2 ˙ − accumulation in the gossypol Schiff base-treated tobacco leaves was at least partially related to the O2 ˙ − produced by the compound. Accordingly, gossypol compounds achieved their anti-TMV activities by stimulating O2 ˙ − accumulation in the tobacco, which was induced either by the O2 ˙ − production or by the chirality of the gossypol compounds, and this result could also explain why (−)-gossypol or gossypol Schiff bases displayed higher anti-TMV activities than (+)-gossypol.